Automated analysis and design of prestressed concrete structures - Pajaron, Crispin C., Jr.; Worsak Kanok-Nukulchai; Ogawa, Junji; Ping Kunawatsatit; Federal Government of Germany (Bangkok : Asian Institute of Technology, 1981)
Automated analysis and design of prestressed concrete frame structures, using the Finite Element Method, are presented. Frame members are idealized with three-node degenerate deep beam elements, each node having three degrees of freedom. In the element formulation, effects of concrete shear deformation, restressing steel stiffness, and cable slope are taken into account for a more rigorous analysis. The same shape function is employed to interpolate cable eccentricities within the element, thus, a parabolic curve can be exactly represented. Accuracy of the element in predicting the behavior and performance of frame structures due to prestress and applied loads are demonstrated in a series of test examples. In this regard, the element is proven to be efficient because a minimum number of elements may be used in the idealization of continuous beam members. Moreover, with the three nodal eccentricities input, the elastic response of the structure due to prestress can be obtained accurately compared with the traditional method of analysis. The design algorithm using the fully stressed concept and a concordant cable profile is implemented. This limiting case somehow provides an efficient process which can be utilized in preliminary or final design.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Structural frames -- Models; Prestressed concrete construction